Squalyl Crown Ether Self‐Assembled Conjugates: An Example of Highly Selective Artificial K+ Channels. Issue 6 (7th January 2016) - Sun, Zhanhu; Gilles, Arnaud; Kocsis, Istvan; Legrand, Yves‐Marie; Petit, Eddy; Barboiu, Mihail
Abstract: The natural KcsA K + channel, one of the best‐characterized biological pore structures, conducts K + cations at high rates while excluding Na + cations. The KcsA K + channel is of primordial inspiration for the design of artificial channels. Important progress in improving conduction activity and K + /Na + selectivity has been achieved with artificial ion‐channel systems. However, simple artificial systems exhibiting K + /Na + selectivity and mimicking the biofunctions of the KcsA K + channel are unknown. Herein, an artificial ion channel formed by H‐bonded stacks of squalyl crown ethers, in which K + conduction is highly preferred to Na + conduction, is reported. The K + ‐channel behavior is interpreted as arising from discreet stacks of dimers resulting in the formation of oligomeric channels, in which transport of cations occurs through macrocycles mixed with dimeric carriers undergoing dynamic exchange within the bilayer membrane. The present highly K + ‐selective macrocyclic channel can be regarded as a biomimetic alternative to the KcsA channel. Abstract : Artificial ion channel : An ion channel formed by H‐bonded stacks of squalyl crown ethers shows high selectivity for K + over other alkali metal ions (see figure) and can be regarded as a a biomimetic alternative to natural KcsA K + channels.